2012
DOI: 10.1016/j.virol.2011.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the DENV-2 type-specific and DEN complex-reactive antigenic sites among DENV-2 genotypes

Abstract: The envelope (E) protein is composed of three domains (ED1, ED2 and ED3) with ED3 targeted by the most potent neutralizing antibodies. DENV-2 strains can be divided into six genotypes. Comparison of ED3 of representative strains of the six genotypes revealed that there are nine variable residues that are specific to a given genotype. Recombinant ED3s (rED3s) of six different DENV-2 strains representing all nine variable residues were expressed, and their reactivity against a panel of two DENV-2 type-specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
(70 reference statements)
0
14
0
1
Order By: Relevance
“…Many strongly neutralizing monoclonal antibodies (mAbs) recognize epitopes located on the lateral ridge (e.g., 3H5-1) or the A-strand (e.g., MA1-27093) (34)(35)(36). EDIII sequences from PDK53/16681 and D2Y98P-PP1 were compared and found to differ by a single residue (N→S) at position 390 (Supplemental Figure 2), which was reported before as a variable position not critical for the binding of DENV2 type-specific or DENV complex-reactive antibodies (37). Based on 6 PFU D2Y98P-PP1 challenge.…”
Section: Resultsmentioning
confidence: 76%
“…Many strongly neutralizing monoclonal antibodies (mAbs) recognize epitopes located on the lateral ridge (e.g., 3H5-1) or the A-strand (e.g., MA1-27093) (34)(35)(36). EDIII sequences from PDK53/16681 and D2Y98P-PP1 were compared and found to differ by a single residue (N→S) at position 390 (Supplemental Figure 2), which was reported before as a variable position not critical for the binding of DENV2 type-specific or DENV complex-reactive antibodies (37). Based on 6 PFU D2Y98P-PP1 challenge.…”
Section: Resultsmentioning
confidence: 76%
“…Thus, DENV requires the conservation of important functional residues that mediate this interaction. Interestingly, the critical antibody-binding residues in ED3 are conserved throughout the six DENV-2 genotypes and reside in regions hypothesized to play roles in the entry of DENV into both mammalian and mosquito cells (Chen et al, 1997;Erb et al, 2010;Hung et al, 2004;Pitcher et al, 2012). Specifically, the role of the ED3 F-G loop (containing the critical residue P384) for entry into C6/36 cells (mosquito larva) was demonstrated by an F-G loop peptide that blocked viral infection of C6/36 cells (Hung et al, 2004).…”
mentioning
confidence: 99%
“…1b). The G330D substitution occurs naturally and is characteristic of the DENV-2 sylvatic genotype (Chambers et al, 1990;Pitcher et al, 2012;Sukupolvi-Petty et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using mAbs indicated that the potent neutralizing capacity was impacted by the genotype-dependent conformational change/exposure of the CC9 loop epitope in DIII (Austin et al, 2012). The natural occurring genotype-or straindependent amino acid variations in DIII have been demonstrated to affect the binding and neutralization of typespecific mAbs of DENV (Pitcher et al, 2012 The LAV SA14-14-2 possesses advantages of satisfactory immunogenicity, low vaccination dose and low cost of production compared with the inactivated vaccine. It has the largest Japanese encephalitis vaccine market share worldwide and further improvement in vaccine efficacy would be meaningful.…”
Section: Bhk-21 C6/36mentioning
confidence: 99%